The impact of regulation and competition on the adoption of fibre-based broadband services: Recent evidence from the European Union member states - Wolfgang Briglauer (International Telecommunications Society (ITS), 2013)
Fibre deployment of next-generation high-speed broadband networks is considered to be a decisive development for any information-based society, yet investment activities and especially the adoption of fibre-based broadband services take place only very gradually in most countries. This work employs static and dynamic model specifications and identifies the most important determinants of the adoption of fibre-based broadband services with recent panel data from the European Union member states for the years from 2004 to 2012. The results show that the more effective previous broadband access regulation is, the more negative the impact on adoption, while competitive pressure from mobile networks affects adoption in a non-linear manner. It appears that the approach of strict cost-based access regulation embedded in the EU regulatory framework is at odds with the targets outlined in the European Commission's Digital Agenda. Finally, we also find evidence for substantial network effects underlying the adoption process.
Keywords: 330; Next-generation telecommunications networks; regulation; competition; adoption; network effects